Impaired cardiac and skeletal muscle bioenergetics in children, adolescents, and young adults with Barth syndrome. Issue 3 (14th February 2017) - Bashir, Adil; Bohnert, Kathryn L.; Reeds, Dominic N.; Peterson, Linda R.; Bittel, Adam J.; de las Fuentes, Lisa; Pacak, Christina A.; Byrne, Barry J.; Cade, W. Todd
Abstract: Barth syndrome (BTHS) is an X‐linked condition characterized by altered cardiolipin metabolism and cardioskeletal myopathy. We sought to compare cardiac and skeletal muscle bioenergetics in children, adolescents, and young adults with BTHS and unaffected controls and examine their relationships with cardiac function and exercise capacity. Children/adolescents and young adults with BTHS ( n = 20) and children/adolescent and young adult control participants ( n = 23, total n = 43) underwent 31 P magnetic resonance spectroscopy ( 31 P‐MRS) of the lower extremity (calf) and heart for estimation of skeletal muscle and cardiac bioenergetics. Peak exercise testing (VO2peak ) and resting echocardiography were also performed on all participants. Cardiac PCr/ATP ratio was significantly lower in children/adolescents (BTHS: 1.5 ± 0.2 vs. Control: 2.0 ± 0.3, P < 0.01) and adults (BTHS: 1.9 ± 0.2 vs. Control: 2.3 ± 0.2, P < 0.01) with BTHS compared to Control groups. Adults (BTHS: 76.4 ± 31.6 vs. Control: 35.0 ± 7.4 sec, P < 0.01) and children/adolescents (BTHS: 71.5 ± 21.3 vs. Control: 31.4 ± 7.4 sec, P < 0.01) with BTHS had significantly longer calf PCr recovery ( τ PCr) postexercise compared to controls. Maximal calf ATP production through oxidative phosphorylation (Qmax‐lin) was significantly lower in children/adolescents (BTHS: 0.5 ± 0.1 vs. Control: 1.1 ± 0.3 mmol/L per sec, P < 0.01) and adults (BTHS: 0.5 ± 0.2 vs. Control: 1.0 ± 0.2 mmol/L sec, P < 0.01) with BTHS compared to controls. Blunted cardiac and skeletal muscle bioenergetics were associated with lower V O2peak but not resting cardiac function. Cardiac and skeletal muscle bioenergetics are impaired and appear to contribute to exercise intolerance in BTHS. Abstract : Cardioskeletal bioenergetics, measured by 31P magnetic resonance spectroscopy (31PMRS), are impaired and appear to contribute to exercise intolerance in children, adolescents and young adults with Barth syndrome. 31P‐MRS quantifies in vivo mitochondrial impairments and might be an important biomarker/outcome measure in future intervention studies in Barth syndrome.